Evolution of preclinical characterization and insights into clinical pharmacology of checkpoint inhibitors approved for cancer immunotherapy. Issue 8 (7th June 2022) - Kasichayanula, Sreeneeranj; Mandlekar, Sandhya; Shivva, Vittal; Patel, Maulik; Girish, Sandhya
Abstract: Cancer immunotherapy has significantly advanced the treatment paradigm in oncology, with approvals of immuno‐oncology agents for over 16 indications, many of them first line. Checkpoint inhibitors (CPIs) are recognized as an essential backbone for a successful anticancer therapy regimen. This review focuses on the US Food and Drug Administration (FDA) regulatory approvals of major CPIs and the evolution of translational advances since their first approval close to a decade ago. In addition, critical preclinical and clinical pharmacology considerations, an overview of the pharmacokinetic and dose/regimen aspects, and a discussion of the future of CPI translational and clinical pharmacology as combination therapy becomes a mainstay of industrial immunotherapy development and in clinical practice are also discussed.